Position statement on youth resistance training: the 2014 International Consensus. Issue 7 (20th September 2013) - Lloyd, Rhodri S; Faigenbaum, Avery D; Stone, Michael H; Oliver, Jon L; Jeffreys, Ian; Moody, Jeremy A; Brewer, Clive; Pierce, Kyle C; McCambridge, Teri M; Howard, Rick; Herrington, Lee; Hainline, Brian; et al.
Abstract : The current manuscript has been adapted from the official position statement of the UK Strength and Conditioning Association on youth resistance training. It has subsequently been reviewed and endorsed by leading professional organisations within the fields of sports medicine, exercise science and paediatrics. The authorship team for this article was selected from the fields of paediatric exercise science, paediatric medicine, physical education, strength and conditioning and sports medicine.